Влияние термообработки тонкой никелид титановой проволоки на ее функциональные и механические свойства - Ковалева, Марина Андреевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
This paper presents the results of experimental studies of the mechanical behavior of thin nickel-titanium wire after heat treatment in various modes. In the experiments, a current wire of 100 µm was used, with different annealing temperatures (from 300 °C to 600 °C) for 5 min. The deformation diagrams of wire tension before failure and in the load-unload cycle were obtained. The resulting diagrams made it possible to reveal the change in some characteristics as a result of annealing.